Cadena de suministro: distribución instantánea, transporte y almacenamiento - Orellana Arimuya, Ivar Salvador (2022)
This paper seeks to publicize the benefits of using the administrative tool called supply chain. Some basic concepts of business administration and what are the tools developed by it have been addressed. Although the concept of supply chain emerged in the 1980s, it was between 1990 and 2000 that its spectrum broadened. At present, it has been widely used in different organizations as a tool that seeks to generate competitive advantages in a globalized world. The supply chain involves all the aspects (direct and indirect) that are necessary to satisfy the needs of the organization or company to produce goods and services, as well as to satisfy the needs of customers (distribution and/or storage). The supply chain seeks effectiveness and efficiency, reducing costs and making zero errors. A sol saved in production or distribution or storage means an extra utility sol. Here is the importance of designing and implementing an adequate supply chain in the organization or company.